JAJANAN PASAR DEMOCRACY - Wargaslot, Rahma (JOURNAL HEALTH AND NUTRITIONS, 2017)
ABSTRACTThe value of democracy in the context of food systems reflects equality in food choices, availability of information, sustainability, engagement, and higher levels of satisfaction. In reality, the development of the street food industry tends to steer people away from the concept of democracy. Vendors barely play a role in the food supply chain because their roles have been replaced by advanced food producers. Their important role in the food system has been replaced by other sectors within the industrial food system, such as large supermarkets and food retailers. This means that equal rights as a concept of democracy have been restricted. This essay illustrates a comparison between two major food provision locations, namely large supermarkets. This essay examines the concept of jajanan pasar and democracy in both locations and provides further exploration of how the implementation of "street food democracy" applies in both locations. Keywords: Food, Democracy, Market ABSTRAK Nilai demokrasi dalam konteks sistem pangan mencerminkan kesetaraan dalam pilihan makanan, ketersediaan informasi, keberlanjutan, keterlibatan dan tingkat kepuasan yang lebih tinggi. Pada kenyataannya, perkembangan industri makanan jajanan pasar cenderung membuat orang menjauh dari konsep demokrasi. Penjual hampir tidak berperan dalam rantai pasokan makanan karena peran mereka telah digantikan oleh produsen makanan yang canggih. Peran penting mereka dalam sistem pangan telah digantikan oleh sektor lain yang tergabung dalam sistem pangan industri seperti supermarket besar dan pengecer makanan. Ini berarti bahwa persamaan hak sebagai konsep demokrasi telah dibatasi. Esai ini menggambarkan perbandingan antara dua lokasi penyediaan makanan utama yaitu supermarket besar. Esai ini mengkaji konsep 'jajanan pasar' dan 'demokrasi' di kedua lokasi tersebut, dan memberikan eksplorasi lebih lanjut tentang bagaimana penerapan 'demo jajanan pasar' di kedua lokasi tersebut. Kata kunci: Makanan, Demokrasi, Pasar==>>Daftar & Demo<<==